Antibacterial Effectiveness Test of Ethanol Extract of Torch Ginger (Etlingera elatior) Flower Against the Growth of Escherichia coli and Staphylococcus aureus - Simatupang, Steffanie Ruth; Panjaitan, Ivonne Mona Selly (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Antibiotic-resistant bacteria like Staphylococcus aureus and Escherichia coli are becoming more common, which is a major worldwide health concern. The purpose of this study was to assess the antibacterial activity of Etlingera elatior (kecombrang flower) ethanolic extract against Gram-positive S. aureus and Gram-negative E. coli. The Microbiology Laboratory at Universitas Advent Indonesia's Faculty of Mathematics and Natural Sciences was the site of the experimental study. Using the disc diffusion method on Mueller Hinton Agar medium, the extract was tested at three concentrations (30%, 40%, and 50%) after being made using the maceration process with 95% ethanol. As demonstrated by inhibitory zones at all doses, the ethanolic extract of E. elatior demonstrated antibacterial activity against both bacterial species. The inhibition zone diameters ranged from 8.95–10.70 mm for E. coli and 9.00–13.68 mm for S. aureus. Statistical analysis using One-Sample t-test confirmed that all treatments significantly inhibited bacterial growth (p < 0.05). Different extract concentrations had a significant effect on S. aureus (p = 0.003) but no significant effect on E. coli (p = 0.083), according to a one-way ANOVA. Because Gram-positive bacteria have simpler cell walls that facilitate the better penetration of bioactive substances like flavonoids, tannins, and saponins, our results show that Etlingera elatior extract has more antibacterial action against S. aureus than E. coli. For the creation of environmentally friendly phytopharmaceuticals, Etlingera elatior can be regarded as a promising natural antibacterial agent.